ANALISIS PERAMALAN JUMLAH PERMINTAAN DARAH DI UNIT TRANFUSI DARAH (UTD) KOTA SEMARANG - Hendrani Ismanto; Wellie Sulistijanti (Universitas Muhammadiyah Semarang, 2018)
Blood is an important component that plays a role in bringing nutrients and oxygen to all organs of the body. The demand for blood supply is increasing every year as population increases are no exception in Semarang. To anticipate the amount of blood demand that is uncertain, a model is needed that can predict the amount of blood demand. The method used is the Box-Jenkins ARIMA method, the object to be studied is the demand for blood types at the Indonesian Red Cross Blood Transfusion Unit (UTD) in the city of Semarang in 2011-2016. The results obtained are blood demand data can be predicted using the ARIMA Box-Jenkins method with the ARIMA model (1,1,0). Keywords: Darah, ARIMA Box-Jenkins, Peramalan, Semarang